The practical Shakespeare : the plays in practice and on the page - Butler, Colin (Ohio University Press, 2005)
A comprehensive treatment of Shakespeare's plays in clear prose, The Practical Shakespeare: The Plays in Practice and on the Page illuminates for a general audience how and why the plays work so well. Noting in detail the practical and physical limitations the Bard faced as he worked out the logistics of his plays, Colin Butler demonstrates how Shakespeare incorporated and exploited those limitations to his advantage: his management of entrances and exits; his characterization technique; his handling of scenes off stage; his control of audience responses; his organization of major scenes; and his use of prologues and choruses. A different aspect of the plays is covered in each chapter?and all chapters are free-standing, for separate consultation. For easy access, chapters also are subdivided, and each part has its own heading. Butler draws most of his examples from mainstream plays, such as Macbeth, Othello, and Much Ado About Nothing. He brings special focus to A Midsummer Night's Dream, which is treated as one of Shakespeare's most important plays. Butler supports his major points with quotations, so readers can understand an issue even if they are unfamiliar with the particular play being discussed. The author also cross-references dramatic devices among plays, increasing enjoyment and understanding of Shakespeare's achievements. Clear, jargon-free, easy-to-use, and comprehensive, The Practical Shakespeare looks to the elements of stagecraft and playwriting as a conduit for students, teachers, and general audiences to engage with, understand, and appreciate the genius of Shakespeare. Colin Butler, previously the head of an English department at a British grammar school, lives in Canterbury, England, where he writes on literary subjects.